A new insight into the impact of systemic lupus erythematosus on oocyte and embryo development as well as female fertility - Mao, Ruolin; Wang, Xiangfei; Long, Rui; Wang, Meng; Jin, Lei; Zhu, Lixia (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is often associated with adverse reproductive outcomes. But it’s currently unclear regarding the role of SLE in oocyte and embryonic development. Also, it’s controversial whether SLE has an adverse effect on fertility. There is a lack of comprehensive understanding and assessment of fertility in patients with SLE. This study was aim to investigate oocyte and embryonic development as well as ovarian reserve, and clinical outcomes in SLE patients during in vitro fertilization (IVF) treatment. By combining data on embryonic and gamete development in SLE patients, we hope to provide new insights into a comprehensive assessment of fertility in SLE patients. In this study, we collected data from 34 SLE patients who were previously diagnosed and in remission for a total of 44 IVF cycles and matched 102 infertile women with a total of 148 IVF cycles by Propensity Score Matching (PSM) of 1:3 ratio. We then evaluated baseline characteristics, ovarian reserve, IVF laboratory outcomes, and clinical outcomes between the two groups. After PSM matching, baseline characteristics including age, infertility types, and duration, as well as infertility causes overall coincided between the two groups. Anti-müllerian hormone (AMH) was significantly lower in the SLE group vs comparison (1.9 vs. 3.3 ng/mL, P=0.001). The SLE group performed a significant reduction in available embryo rate (76.6% vs. 86.0%, P=0.001), good-quality blastocyst formation rate (35.1% vs. 47.0%, P=0.003), and blastocyst formation rate (51.0% vs. 67.7%, P=0.001) compared to the comparison. As for clinical outcomes, the implantation rate in the SLE group was notably lower (37.9% vs. 54.9%, P=0.022). The CLBR following every embryo-transfer procedure was distinctly lower (41.2% vs 68.6%, P=0.016) in the SLE group vs comparison. Also, the conservative and optimal CLBRs following every complete cycle procedure were significantly reduced in the SLE group vs the comparison (P=0.001, both). Patients with SLE present worse outcomes in oocyte and embryonic development, thus yielding compromised female fertility and clinical pregnancy. Individualized fertility assessment and early fertility guidance are necessary for these special groups.